1) root 6 . root 3 = root 3 . 2 . root 3

Clearly, root 3 . root 3 = 3

Hence, Answer = 3 root 2.

2) root 6 / root 2 = root 3 . 2 / root 2 = root 3

3 ) root 8 + 2 rooot 18 - root 98

2 root 2 + 2 . 3 . root 2 - 7 root 2

2 root 2 + 6 root 2 - 7 root 2

root 2

4) root 2 ( root 8 + root 2 ) ^2

root 2 ( 8 + 2 + 2 root 8 . root 2 )

root 2 ( 10 + 8 )

18 root 2

I don't understand.

How should I explain.

Let me tell you.'

root ( 6 ) = root ( 2 x 3 ) = root 2 . root 3

root 3. root 3 = 3

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up